Histopathological and Hematological Effect of Silver Nanoparticles against acute Escherichia coli Infection in Male Rats - Ghusoon A.A Alneamah (Journal of Global Pharma Technology, 2016)
The potential treatments of silver have known long time ago. Recently many researchers have used silver nanoparticles in the area of medication because their antimicrobial, bio affinities and their easy ways to synthesis. In the present study we have estimated the antimicrobial and hematological effect of silver nanoparticles (AgNps) against acute E.coli infection in male rats. firstly the Ag Nps was synthetic and characterization by SEM which reviled size in about 25 nm in diameter, UV-vis have shown peak absorption in 410 nm. (40) Male rats use in the experiment was divided equally into (4) groups as following (n=10): Group I: Rats served as control and gavage   0.4 ml/ rat from distilled waters   for three days. Group II: Rats served as experimental and gavage 0.4 ml/rats  from AgNps for three days .Group III: Rats  infected with E. coli  ( 0.2)ml/rat single dose  (I/P).Group IV: Rats  infected with1×10 9CFU of E.coli (0.2)ml/rat   single dose  (I/P ) +  gavage 0.4 ml/rats from AgNps  for three days. After three days the animals were sacrificed, the blood collected directly from the heart for hematological analysis, and the specimens from liver, and intestine were dissected out for histopathological examination. The hematological results showed significant decrease in RBCs, Hb compared with control group and increase in WBCs in infected group compared with infected group .While this value improved in group (II, IV). Regarding the histopathological results the infected group showed inflammatory cells infiltration, necrosis, and hemorrhage in both organs and micro thrombi in liver. After treatment with AgNps showed improvement in the both hematological and histological parameters.Keywords: Silver nanoparticles (AgNps), Escherichia coli, Histopathology, Rats.